2018
DOI: 10.4269/ajtmh.17-0438
|View full text |Cite
|
Sign up to set email alerts
|

Health Status of Asylum Seekers, Spain

Abstract: The rising rate of conflicts and the unsafe situation caused by reasons of ethnicity, religion, gender, sexual orientation, political opinion, or nationality entail an increase in the number of migratory movements. The goal of this article is to describe the health status of asylum seekers visited in an international health center. We conducted a retrospective study of the asylum seekers visited between July 2013 and June 2016. A total of 303 cases were included. The median age was 28.0 years (interquartile ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
(33 reference statements)
1
19
0
Order By: Relevance
“…Eleven studies evaluated the presence of S. stercoralis infection only through the investigation of larvae in faeces (Table 1) [11][12][13][14][15][16][17][18][19][20][21]. The most frequently used microbiological techniques were microscopic examination of faeces by concentration techniques (the Ritchie method) and/or specific larvae culture (the Koga agar plate).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies evaluated the presence of S. stercoralis infection only through the investigation of larvae in faeces (Table 1) [11][12][13][14][15][16][17][18][19][20][21]. The most frequently used microbiological techniques were microscopic examination of faeces by concentration techniques (the Ritchie method) and/or specific larvae culture (the Koga agar plate).…”
Section: Resultsmentioning
confidence: 99%
“…After duplicate articles were removed, 495 articles were screened for potential eligibility by title and abstract, and 48 articles were selected for full‐text review (see flow diagram in Figure ). Finally, 24 studies were included in the review and meta‐analysis, comprising 12 386 screened people . Main characteristics of the included studies are summarised in Tables and .…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the low mean age of our group; there is also the possibility that in a transit population, in which people prioritize basic needs, those with mild symptoms on board may not recount. In addition, the hardness of the migratory process in general, an particularly of this route, makes that the people who carry it out are generally healthy [29]. Management of these conditions in a mobile context is highly challenging, as discontinuation of chronic controls and medications may cause exacerbations of previously well controlled non communicable diseases [30], which globally account for 63% of deaths, including 14 million people of premature deaths [31].…”
Section: Discussionmentioning
confidence: 99%
“…Administrative issues and stigma were also identified as important barriers in our study, although to a lesser degree (30%). These barriers could lead to delays in diagnosing and treating different diseases that carry not only individual, but important public health consequences such as tuberculosis, HIV, hypertension, diabetes, hepatitis B and C, schistosomiasis, strongyloidiasis, and Chagas ( 36 ). For example, in the previously mentioned study of migrants with HIV ( 35 ), 14–25% of migrants who reported barriers to healthcare access had been diagnosed with late HIV.…”
Section: Discussionmentioning
confidence: 99%